2019
DOI: 10.1111/pbi.13098
|View full text |Cite
|
Sign up to set email alerts
|

Transformation strategies for stable expression of complex hetero‐multimeric proteins like secretory immunoglobulin A in plants

Abstract: Summary Plant expression systems have proven to be exceptional in producing high‐value complex polymeric proteins such as secretory IgAs ( SI gAs). However, polymeric protein production requires the expression of multiple genes, which can be transformed as single or multiple T‐ DNA units to generate stable transgenic plant lines. Here, we evaluated four strategies to stably transform multiple genes and to obtain high expression of all components. Using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In many cases, co-expression of two or more proteins is required to produce biologically active pharmaceutical proteins, such as monoclonal antibodies, IgA, or multi-component virus like particles (Thuenemann et al, 2013;Palaci et al, 2019). To further improve the utility of plant-based systems, we have FIGURE 7 | Characterization of c2A10G6.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, co-expression of two or more proteins is required to produce biologically active pharmaceutical proteins, such as monoclonal antibodies, IgA, or multi-component virus like particles (Thuenemann et al, 2013;Palaci et al, 2019). To further improve the utility of plant-based systems, we have FIGURE 7 | Characterization of c2A10G6.…”
Section: Discussionmentioning
confidence: 99%
“…As to several mucosal pathogens, it has been reported that pathogen-specific IgA can prevent infection 31 , 41 45 . As to Stx, previous studies indicated that mucosal vaccination could prevent disease and induce production of toxin-specific IgA antibodies, however, the effect of passively administered Stx-specific IgA was not clarified 33 , 39 , 46 .…”
Section: Discussionmentioning
confidence: 99%
“…To obtain simplified SIgA antibodies (sSIgAs), the J chain and secretory component have to be co-expressed with the VHH-IgA molecule [7][8][9]. Several methods could be used for introducing the three genes in the same cell, such as simultaneous introduction -as a tandem construct or triple co-transformation, or rather successive introduction -either by successive supertransformation or genetic crossing.…”
Section: How To Simplify the Production Of Igg And Siga Antibodies?mentioning
confidence: 99%
“…Several methods could be used for introducing the three genes in the same cell, such as simultaneous introduction -as a tandem construct or triple co-transformation, or rather successive introduction -either by successive supertransformation or genetic crossing. In dicot seeds, the highest level of sSIgA expression has been obtained by first identifying transformants expressing high amounts of both the J chain and the secretory component, and super-transforming or crossing them with plants expressing the bivalent monomeric VHH-IgA molecule [8]. Indeed, expression of several genes in the same plant cell, even if the same promoter is used, does not necessarily result in the same amounts of transcripts or co-translated constituent protein chains of the sSIgA.…”
Section: How To Simplify the Production Of Igg And Siga Antibodies?mentioning
confidence: 99%